Thematic Learning in the Independent Curriculum in Elementary Schools Based on the Islamic Montessori Method for Multiple Intelligence - Wijaya, Krisna; Wijaya, Ridho Gata; Huwaida, Jaziela; Rochmat, Cecep Sobar (Universitas Pendidikan Ganesha, 2024)
Recently, the practice of categorizing intelligent students and unintelligent students is a deeply ingrained phenomenon within the realm of education in Indonesia. Indeed, multiple specialists have verified that the attributes of intelligence vary among individual students. Hence, this study aims to revolutionize theme education in primary schools by implementing an autonomous curriculum that is rooted in the Islamic Montessori for Multiple Intelligence approach. This study employs the library research methodology, utilizing primary and secondary data derived from printed or digital sources such as books, journals, and magazines. The outcome of this discussion is to generate a set of activities for different domains of learning. These activities include folding clothes or buttoning clothes for the Islamic Studies domain, hand washing for the practical life domain, matching pictures with zones for the sensorial domain, matching words for the language domain, matching numbers for the mathematical domain, matching fruit with pictures for the cultural realm, and drawing or creating ecobricks for the arts & crafts realm. These diverse educational approaches involve the creation of a curriculum centered around the Islamic Montessori for Multiple Intelligence method, with the aim of promoting a healthy and virtuous lifestyle. These methods can be effectively utilized by teachers during classroom instruction. Through the development of diverse learning activities, education will be conducted in a more comprehensive manner, tailored to the individual traits and capabilities of each student. This approach to designing educational activities can thereafter be implemented in the instruction of young children in primary schools.